2021
DOI: 10.3390/su13148070
|View full text |Cite
|
Sign up to set email alerts
|

Reusing Geopolymer Waste from Matrices Based on Metakaolin or Fly Ash for the Manufacture of New Binder Geopolymeric Matrices

Abstract: The increasing use of geopolymer materials in the construction and civil engineering sectors generates a large amount of non-biodegradable waste that will end up in landfills. It is therefore necessary to anticipate solutions for the proper management of this waste. In this work, new geopolymer materials were fabricated by partially replacing the reactive raw minerals (fly ash, FA, or metakaolin, MK) with used geopolymers (fully fly ash-based, FAref, or metakaolin-based, MKref), in order to develop a strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…The preparation of geopolymer materials was carried out in accordance with our previous study [ 8 ]. The procedure for geopolymer preparation is shown in Figure 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of geopolymer materials was carried out in accordance with our previous study [ 8 ]. The procedure for geopolymer preparation is shown in Figure 4 .…”
Section: Methodsmentioning
confidence: 99%
“…These studies generally remain within the framework of a single approach, which consists in reusing the waste in the form of aggregates to replace natural aggregates (sand or gravel) in order to produce mortars or concretes. Hattaf et al [ 8 ] proposed to reuse geopolymer waste as a substitute for the starting raw materials (metakaolin and fly ash) to produce new geopolymer matrices. These authors demonstrated that high compressive strengths can be maintained for substitution rates up to 40 wt% (compressive strengths greater than 43 MPa).…”
Section: Introductionmentioning
confidence: 99%
“…The fine-grained waste material generated during processing is transported to and deposited in landfills. Therefore, geopolymer was produced using different waste materials, and its properties were investigated in previous studies [4][5][6][7]. The sodium hydroxide (SH) and sodium silicate (SS) used in this study were close to the amounts of SH and SS used in these studies.…”
Section: Introductionmentioning
confidence: 93%
“…Few works dedicated to this theme have been identified in the literature [ 24 , 25 , 26 , 27 , 28 , 29 ]. In a recent study [ 24 ], we investigated the possibility of partially replacing fly-ash (FA) or metakaolin (MK) with Fly-ash-based Recycled Geopolymer (FARG) and Metakaolin-based Recycled Geopolymer (MKRG) wastes in order to manufacture new geopolymer matrices that consume less raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…Few works dedicated to this theme have been identified in the literature [ 24 , 25 , 26 , 27 , 28 , 29 ]. In a recent study [ 24 ], we investigated the possibility of partially replacing fly-ash (FA) or metakaolin (MK) with Fly-ash-based Recycled Geopolymer (FARG) and Metakaolin-based Recycled Geopolymer (MKRG) wastes in order to manufacture new geopolymer matrices that consume less raw materials. Fine-grained powders of FARG and MKRG were used in the partial substitution of the sources of aluminosilicates FA and MK up to a mass rate of 50% to produce three formulations of binders referenced as FA/FARG, MK/MKRG and MK/FARG.…”
Section: Introductionmentioning
confidence: 99%